Determinant of Tourist Satisfaction on Halal Tourism: Examining the Religious Aspect as a Moderating Variable - Wibowo, Muhammad Ghafur; Khoiruddin, Akhmad Yusuf (EKONOMIKA SYARIAH : Journal of Economic Studies, 2022)
The objectives of this study are to test the relationship between tourism motivations and tourist satisfaction, and to test how ‘Religion’ moderates the relationship in Bukittinggi City, West Sumatera. The variable ‘Religion’ is represented by the availability of Islamic norms and practices which are relevant to tourism at the destination. The results of the Partial least square (PLS) indicated that the tourism motivations are significantly and positively related to tourist satisfaction. The results also showed that Islamic attribute significantly affect the tourist satisfaction. Travel motivation consisting of pull motivation and push motivation has also been shown to have a significant effect on tourist satisfaction.Tujuan dari penelitian ini adalah untuk menguji hubungan antara motivasi wisata dan kepuasan wisatawan, dan untuk menguji bagaimana 'Agama' memoderasi hubungan tersebut. Studi kasus dalam Penelitian ini adalah Halal Tourism di Kota Bukittinggi, Sumatera Barat. Variabel ‘Agama’ diwakili oleh tersedianya norma dan praktik Islam yang relevan dengan pariwisata di destinasi. Hasil Partial least square (PLS) menunjukkan bahwa motivasi wisata berhubungan positif dan signifikan dengan kepuasan wisatawan. Hasil penelitian juga menunjukkan bahwa atribut Islami berpengaruh signifikan terhadap kepuasan wisatawan. Motivasi perjalanan yang terdiri dari motivasi tarikan dan motivasi dorongan juga terbukti memiliki pengaruh yang signifikan terhadap kepuasan wisatawan.